Optimal consumption and portfolio choice with ambiguity - Qian Lin; Frank Riedel (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
We consider optimal consumption and portfolio choice in the presence of Knightian uncertainty in continuous-time. We embed the problem into the new framework of stochastic calculus for such settings, dealing in particular with the issue of non-equivalent multiple priors. We solve the problem completely by identifying the worst-case measure. Our setup also allows to consider interest rate uncertainty; we show that under some robust parameter constellations, the investor optimally puts all his wealth into the asset market, and does not save or borrow at all.
urn:nbn:de:0070-pub-26753210
Keywords: 330